2002
DOI: 10.1080/01140671.2002.9514193
|View full text |Cite
|
Sign up to set email alerts
|

Multiple shoot formation in lentil (Lens culinaris) seeds

Abstract: A protocol based on seed culture was developed for efficient in vitro propagation of lentil (Lens culinaris Medik). Benzyladenine (BA), thidiazuron (TDZ), and kinetin all induced multiple shoot formation. In terms of the number of long shoots (>2.0 cm) produced per seed, BA and TDZ at optimum concentrations (0.2-0.4 and 0.1 mg/litre, respectively) had similar efficiency, whereas kinetin produced less shoots. Murashige and Skoog (MS) salt composition was better than that of Gamborge (B5) for shoot induction. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 9 publications
2
8
0
Order By: Relevance
“…Earlier reports on micropropagation of different leguminous species have also used B 5 medium for shoot induction [21]- [23]. In contrast to our results, B 5 medium was found to be less effective than MS and WP medium in leguminous species, viz., Swartzia madagascariensis [24] and Lens culinaris [25]. Our results are also in agreement with earlier workers, who have used B 5 medium for in vitro shoot formation in other species.…”
Section: Effect Of Nutrient Mediasupporting
confidence: 93%
“…Earlier reports on micropropagation of different leguminous species have also used B 5 medium for shoot induction [21]- [23]. In contrast to our results, B 5 medium was found to be less effective than MS and WP medium in leguminous species, viz., Swartzia madagascariensis [24] and Lens culinaris [25]. Our results are also in agreement with earlier workers, who have used B 5 medium for in vitro shoot formation in other species.…”
Section: Effect Of Nutrient Mediasupporting
confidence: 93%
“…5) and due to these necrotic activities regenerating shoots failed to grow and survive further. To overcome this problem of shoot tip necrosis in chickpea double the concentration of CaCl 2 and KNO 3 were used in MS following the report of Ye et al (2002) as found in case of lentil. Addition of twice the concentration CaCl 2 and KNO 3 in the regeneration medium has been found to prevent the browning of the regenerating shoots during this study thus prevented the necrosis of young shoots.…”
Section: Resultsmentioning
confidence: 99%
“…In order to overcome shoot tip death and to improve shoot health, increased concentration of macro-salts such as CaCl 2 , NH 4 NO 3 and KNO 3 were used in the medium (Ye et al 2002). All media contained 3.0% sucrose with 0.8% agar with pH 5.8, adjusted before autoclaving.…”
Section: Methodsmentioning
confidence: 99%
“…But in most of the cases necrosis was found to occur on the tip of these regenerated shoots and such shoots failed to grow and survive further. To overcome this problem of shoot tip necrosis in chickpea double the concentration of CaCl2 and KNO3 used in MS was added in the regeneration medium following the report of Ye et al (2002) as they could overcome shoot tip death in lentil.…”
Section: Resultsmentioning
confidence: 99%